Dietary Aronia melanocarpa extract enhances mTORC1 signaling, but has no effect on protein synthesis and protein breakdown-related signaling, in response to resistance exercise in rat skeletal muscle - Yuhei Makanae; Satoru Ato; Kohei Kido; Satoshi Fujita (Taylor & Francis Group, 2019)
Background Ursolic acid altered muscle protein metabolism in normal and resting conditions after acute resistance exercise, suggesting that eating fruits rich in ursolic acid could enhance muscle protein synthesis and decrease muscle degradation. Aronia melanocarpa, a member of the family Rosaceae and native to North America and Eastern Canada, is rich in ursolic acid. In this study, we examined the effects of A. melanocarpa extract (AME) supplementation on the mTORC1 signaling pathway and muscle degradation-related factors in rats, both alone and in combination with resistance exercise. Methods Male Sprague-Dawley rats were divided into AME and normal chow (NOR) groups. AME group was fed chow providing a dose of 3 g/kg of AME and 115 mg/kg of ursolic acid for 7 days, whereas NOR rats were fed normal powder chow. The right gastrocnemius muscle of each animal was isometrically exercised (5 sets of ten 3-s contractions, with a 7-s interval between contractions and 3-min rest intervals between sets), while the left gastrocnemius muscle served as an internal control. Western blotting and real-time polymerase chain reaction were used to assess expression of factors involved in the mTORC1 signaling pathway and muscle degradation. Results At 1 h after resistance exercise, phosphorylation of ERK1/2 was significantly increased by AME consumption. At 6 h after resistance exercise, AME consumption significantly increased the phosphorylation of Akt, p70S6K, rpS6, and AMPK. It also increased MAFbx expression. Furthermore, AME significantly increased the phosphorylation of p70S6K and rpS6 in response to resistance exercise. However, AME did not increase muscle protein synthesis (MPS) after resistance exercise. AME did not affect the expression of any of the mediators of protein degradation, with the exception of MAFbx. Conclusions Dietary AME enhanced mTORC1 activation in response to resistance exercise without increasing MPS. Moreover, it neither accelerated muscle protein degradation nor otherwise negatively affected protein metabolism. Further study is needed to clarify the effect of the combination of AME and chronic resistance training on muscle hypertrophy.